The Contingency of Brand Image, Price Perception and Store Atmosphere Towards Consumer Repurchase Intention In the Current Parasocial Setting of Local FnB Bussiness - Febrianto, Rozindo Bima; Parwati, Kardina Yudha (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The growing number of students in Malang City presents a promising market opportunity for the food and beverage (F&B) industry. However, the rapid expansion of this sector has intensified competition, creating numerous alternatives that may reduce customers repurchase intention due to decision inertia. Repurchase intention, as a reflection of customer retention, plays a crucial role in sustaining business competitiveness and continuity. Hondje Tea Shop, an F&B business operating since 2018, offers a “homely” concept that emphasizes comfort over luxury. This study aims to analyze the influence of brand image, price perception, and store atmosphere on repurchase intention among Hondje Tea Shop customers in Malang. Adopting a quantitative approach, the findings reveal that brand image, price perception, and store atmosphere significantly influence repurchase intention. A strong and relatable brand image enhances emotional connection, while fair price perception and a well-designed store atmosphere improve customer satisfaction and encourage repeat purchases.